ADSORPTION BEHAVIOUR OF CITRIC ACID FROM AQUEOUS SOLUTIONS ON ACTI VATED CHARCOAL (Biological Sciences - PJSIR, 2002)
Adsorption of cit ric acid at d i fferent concentration s on acti vated charcoal at 22° has been acconp l_i shed. I t as fou nd that at low concentrations, langm u i r and Freund lich equations arc wel l obeyed. The adsorption oJ citric acid irom aqu eous solution  on  the  surface  of  charcoal   is  mono layer.